Nursing care in the perioperative period for patients undergoing bariatric surgery - Maria Beatriz Guimarães Ferreira; Márcia Marques dos Santos Felix; Cristina Maria Galvão (Universidade Federal do Ceará, 2014)
This integrative review aimed to analyze the available evidence in the literature regarding nursing care in the perioperative period for patients who underwent bariatric surgery. The search for primary studies was carried out in the US National Library of Medicine National Institutes of Health, Cumulative Index to Nursing and Allied Health Literature and Latin American and Caribbean Health Sciences Literature databases. The sample was comprised of 11 primary studies, published between January 2002 and July 2013, and grouped in two categories. The main nursing care activities identified were: bed mobility, ambulation at 12 hours, thromboembolic prophylaxis using compression devices, antibiotic prophylaxis, care for surgical drains, catheters and wound dressings, and guidance for patients regarding pre and postoperative preparation. The difficulties experienced by nurses and the team in the care provided were also discussed.